The Impact of Covid-19 Pandemic on Financial Performance of Companies Go Public in Indonesia - Widiar, RR Wulan Indri; Setyahuni, Suhita Whini (BALANCE: Economic, Business, Management and Accounting Journal, 2023)
This study aims to investigate the difference of financial performances public companies in Indonesia before the COVID-19 outbreak and during the pandemic in 2019 and 2020. This study used 136 public listed firms in Indonesia in 2019 and 2020. The data were tested using one sample paired t-test. The findings shows that there was significant difference on the average revenue and ROA before the COVID-19 outbreak and during the outbreak in 2019 and 2020. The total revenue and ROA were significantly decreased during the pandemic. This study gives a new perspective on the measurement of financial performances during the COVID-19. This study also provides empirical evidence on the financial performances during the COVID-19 outbreak from institutional theory perspective.